A Motivation Practice and Performance in Public Schools of Lalitpur District (Panauti Journal, 2024)
The study appraises current practices of teachers’ motivation and students’ performance in community schools of Lalitpur. The objective of the study is to conceptualized motivation from effective teaching and learning perspectives that fostered students’ performances. The study applied single instrumental case study methodology in which information are generated from in-depth interviews and focus group discussion. During the analysis, the theoretical insights were brought from goal orientation, and need/motivation theories. The study finds that, teachers applying various motivational strategies to the school that increases students’ performances. Students are becoming sensitive on moral value of education; they are questioning on ethical character, subject knowledge and expertise the teaching and parenting. Writing skill and academic performance of the students found in improving trend.